2018
DOI: 10.1055/a-0591-1751
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nerve Fiber Density between Patients with Uterine Leiomyoma with and without Pain: a Prospective Clinical Study

Abstract: Introduction We aimed to compare the presence and the amount of nerve fibers in endometrial, myometrial and leiomyoma tissues using protein gene product 9.5 (PGP 9.5) and neurofilament (NF) immunohistochemical staining in uterine leiomyoma patients with and without pain complaint. Methods Patients undergoing hysterectomy for uterine leiomyoma were prospectively enrolled in the study. Twenty-five uterine leiomyoma patients without pelvic pain complaint (visual analog scale (VAS) < 5) were assigned to Group 1; 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…To this regard, NGF has a pivotal role in the generation of pain and hyperalgesia in many acute and chronic pain states (Hefti et al, 2006;Donnez and Dolmans, 2016); therefore, it may be suggested that, also in fibroids, pelvic pain along with dysmenorrhea may depend on these factors. Even though a significant increase in density of small nerve fibers in the myometrium of women with endometriosis and chronic pelvic pain, along with perivascular nerve fiber proliferation, was detected (Tokushige et al, 2007); more recently published data demonstrated that the quantity and density of nerve fibers in myometrial and leiomyoma tissue in patients with pain were similar to those in patients without pain (Giray et al, 2018) The expression of NGF, MAP-2 and SYP was upregulated in adenomyosis (Carrarelli et al, 2017) and in deep infiltrating endometriosis (Gori et al, 2016), correlated with pain, a typical symptom of uterine disorders; the present study demonstrates a significant increase of all the selected neurogenic markers also in uterine fibroids.…”
Section: Discussionmentioning
confidence: 99%
“…To this regard, NGF has a pivotal role in the generation of pain and hyperalgesia in many acute and chronic pain states (Hefti et al, 2006;Donnez and Dolmans, 2016); therefore, it may be suggested that, also in fibroids, pelvic pain along with dysmenorrhea may depend on these factors. Even though a significant increase in density of small nerve fibers in the myometrium of women with endometriosis and chronic pelvic pain, along with perivascular nerve fiber proliferation, was detected (Tokushige et al, 2007); more recently published data demonstrated that the quantity and density of nerve fibers in myometrial and leiomyoma tissue in patients with pain were similar to those in patients without pain (Giray et al, 2018) The expression of NGF, MAP-2 and SYP was upregulated in adenomyosis (Carrarelli et al, 2017) and in deep infiltrating endometriosis (Gori et al, 2016), correlated with pain, a typical symptom of uterine disorders; the present study demonstrates a significant increase of all the selected neurogenic markers also in uterine fibroids.…”
Section: Discussionmentioning
confidence: 99%
“…The ECM content varies in different ULs and is presumably subject to change as the myoma progresses and undergoes involution [ 14 ]. The main cellular components of a UL are smooth muscle cells, fibroblasts and vascular endothelial cells; other detected cellular components include blood cells, neurons and telocytes [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Ul Cellular Origin and Compositionmentioning
confidence: 99%
“…The McGill Pain Questionnaire collected detailed data about the pain associated with fibroids and evaluated the impact on pain from the study drug injection [35,36]. The visual analogue scale (VAS) for pain was used to evaluate fibroid-related pain on a 0-10 Likert scale (higher score = worse pain) [37,38]. The questionnaires were administered at baseline and post-study drug injection to assess fibroid-related symptoms such as menorrhagia and pain.…”
Section: Patient-reported Outcomesmentioning
confidence: 99%